SECURITY, GEOPOLITICAL CAPABILITY, SOCIETAL RESILIENCE AND THE PUBLIC POLICIES TO ENFORCE IT - Iulian CHIFU (Bulletin of "Carol I" National Defense University, 2022)
Resilience became a concept of first importance for today’s hybrid threats and conventional turbulences, even full-fledged wars in Europe. But since there is a number of theories and definitions of this concept, some type of rationale should be made, as for the instruments needed to measure the level of resilience of states, nations and societies. Moreover,there are a lot of projects, attempts and possibilities to do that, coming from different disciplines and fields of research which also need to be rationalized. More importantly, we need to find a proper set of indicators to show us an actor’s level of resilience in order to therefore propose a solution and public policies to enforce it. That is our aim in a multi-institutional approach to be launched in the near future. The most problematic part is that of finding suitable measurable items in order to describe some of the criteria for resilience that need to be approached in order to create a map of indicators and to deal, therefore, with a resilience level improvement